2005
DOI: 10.1111/j.1365-2929.2005.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of basic clinical skills training on objective structured clinical examination performance

Abstract: OBJECTIVES The aim of curriculum reform in medical education is to improve students' clinical and communication skills. However, there are contradicting results regarding the effectiveness of such reforms.METHODS A study of internal medicine students was carried out using a static group design. The experimental group consisted of 77 students participating in 7 sessions of communication training, 7 sessions of skills-laboratory training and 7 sessions of bedsideteaching, each lasting 1.5 hours. The control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 17 publications
7
71
0
6
Order By: Relevance
“…Studies have shown that SPs can give summative and formative assessments in addition to teaching basic clinical skills. 5,9,[12][13][14] However, given the variability of reported assessments used in ICM courses demonstrated in our survey, the use of the SP as an effective evaluator for both formative and summative assessment needs to undergo further critical appraisal. Given that a large percentage of respondents to the 2005 CDIM survey indicated already using SPs for formative and/or summative evaluations, we believe this area of research should receive a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SPs can give summative and formative assessments in addition to teaching basic clinical skills. 5,9,[12][13][14] However, given the variability of reported assessments used in ICM courses demonstrated in our survey, the use of the SP as an effective evaluator for both formative and summative assessment needs to undergo further critical appraisal. Given that a large percentage of respondents to the 2005 CDIM survey indicated already using SPs for formative and/or summative evaluations, we believe this area of research should receive a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…Kommunikative Fertigkeiten in der Aus-und Weiterbildung (Moore et al 2004;Jün-ger et al 2011) sowie die Fähigkeit zur Empathie können durch entsprechende Trainings nachweislich verbessert werden (Yedidia et al 2003;Jünger et al 2005). Daher haben die Curricula der medizinischen Ausbildungsstätten in den letzten Jahren zahlreiche Reformierungen durchlaufen (vgl.…”
Section: Hintergrundunclassified
“…The evaluation of the clinical skills of medical students is feasible in a standardized manner. Actually the usefulness of simulation-based education has been shown to improve the relationship between patients and students, the clinical activities of the students on the ward, and the safety of medical practice (2)(3)(4)(5).…”
Section: Clinical Skills Training Should Be One Of the Most Importantmentioning
confidence: 99%